Synthesis of gem-difluoromethylenated spiro-γ-butyrolactones by employing PhSCF2Si(CH3)3as a gem-difluoromethylenating agent - Adisak Chatupheeraphat (2018)
PhSCF2TMS was utilized as a useful gem-difluoromethylene building block for the synthesis of gem-difluoromethylenated spiro-γ-butyrolactones. The radical cyclization of γ-alkenyl- γ-gem-difluoro(phenylsulfanyl)methyl-γ-butyrolactones provided gem-difluoromethylenated spiro-γ-butyrolactones. PhSCF2TMS (TMS = trimethylsilyl) is utilized as a gem-difluoromethylenating agent for the synthesis of gem-difluoromethylenated spiro-γ-butyrolactones. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.